Early Life Vaccination of Companion Animal Pets - Dodds, W. Jean (Vaccines (Basel), 2021)
Development of the immune system of mammalian animal species parallels that of humans and involves the innate and adaptive (acquired) immune responses acting together with the thymus gland. Consequently, issues surrounding the adequacy and safety of vaccinations to protect pet animals from their relevant infectious diseases need to be addressed just as they are for humans. Pet animals, especially canines, also have unique needs because of the wide diversity of purebred and mixed breeds that vary greatly in size, type, temperament, and even maturation rates. Furthermore, pets in early life encounter a series of changes that can affect their development and induce stressors including parasite control, new homes and environment, novel foods, and the socialization that is essential at a time when vaccinations need to be given. While recognizing that this overall need is becoming more understood, current vaccination policy guidelines for companion animals are still only adhered to by about 40% of veterinarians worldwide. Clearly, vaccination of pets should no longer be considered as “one size fits all”.